O efeito da substituição parcial de Sn por metais 3d na transição de fase de primeira ordem de ligas Heusler NiMnSn. - López Córdova, Cecilia (2009)
Results reported in the literature show that the martensitic phase transformation (MFT) in the Ni50Mn25Sn25 Heusler alloy can be achieved when an excess of Mn atoms are in the Sn sites1 and the Mn partial substitution by Fe atoms in the martensitic Ni50Mn36Sn14 Heusler alloy results in a reduction of the MFT temperature, being this transformation absent for Fe concentration larger than 10 at. %.19 In this work, we prepared, by arc-melting furnace, two different series of samples, where we studied (i) the Fe localization and magnetism and also the origin of the reduction of the MFT observed after a partial substitution of Mn atoms by Fe in the martensitic Ni50Mn36Sn14 Heusler alloy (Series-A) and (ii) the possibility of MFT occurrence in the Ni50Mn25Sn25 Heusler alloy when Sn atoms are substituted either by Cr or by Fe (Series-B). We characterize our samples by magnetization, scanning electron microscopy and 57Fe Mössbauer spectroscopy. The results show that there is a solubility limit in all partial substitutions done in this work, i.e., Mn substituted by Fe and also Sn substituted either by Cr or by Fe; being the solubility limit more restricted in the Series-B case, since we observed segregated phases in all Series-B samples, even for very low substitution transition metal concentration (Cr or ). We conclude that this segregation effect, observed in both Series-A and B, is responsible for the absence of the MFT observed in our samples. Specially, in Series-B, Cr crystals, with polygonal shapes and sizes of about to , are formed during the phase segregation process in all Cr samples. Our results also allow us to estimate to be about 2% the solubility limit of 57Fe in Mn sites of the L21-structure of the martensitic Ni50Mn36Sn14 Heusler alloy. These 57Fe atoms are magnetic at 300K and have magnetic moment of.